Editorial (Italian Journal of Public Health, 2005)
Excerpt:The complexity of the food and agricultural system, along with the fragmentation, diversification, and de-localization of food production, have give rise to the spread of food related problems across many countries,with complex global implications for food safety and the management of emergencies. Technological developments, the rapid distribution of food, inappropriate regulations and surveillance, have also contributed to these problems.